Influence of Additive Manufacturing Technology on Mechanical Properties of Glass-Filled Fine Polyamide PA3200GF - BAJERSKI, Paweł; PĘCHERSKI, Ryszard (Engineering Transactions, 2017)
Additive manufacturing is a very fast developing field of research and many parts with complicated geometry are now made using 3D printing. The injection molding, casting, milling and other processes have some limitations and low volume of production makes these processes quite expensive. 3D printing allows to fabricate parts with enough mechanical strength and without looking at the above mentioned limitations. Nowadays, designers are able to fabricate prototypes with not only optimized but also complex shape. Unfortunately, the parts made from thermoplastic materials by means of 3D technique have lower mechanical strength in comparison to the parts made by using injection molding process. The orientation of layers, thickness of a layer, porosity, and process parameters have a big influence on mechanical properties of the fabricated parts. In this paper, the experimental results from the static tensile tests, the compression tests and the dynamic three-point bending test are presented. The tests were performed for different orientations of printing specimens. It was shown that to assess the mechanical properties of printing parts (made by using selective laser sintering (SLS) technique)our own measurements need to be obtained. The available catalogue data are not sufficient for further investigations like in the finite element (FE) analyses.